The Design of Tympani Thermometer Using Passive Infrared Sensor - Nur Hudha Wijaya; Zanella Oktavihandani; Kunal Kunal; Elsayed T.Helmy; Phong Thanh Nguyen (Universitas Muhammadiyah Yogyakarta, 2020)
Measuring body temperature depends on the type of thermometer and measured body area. A thermometer placed on the tympanic membrane is considered ideal because the tympanic membrane and hypothalamus have arterial blood supply originating from the carotid artery (neck). Therefore, it is considered directly close to the core temperature. The Tympani Thermometer with external storage can facilitate the doctor's performance in diagnosing patients. This tool is designed using the MLX90614 sensor as a passive infrared sensor that can receive infrared energy from the tympanic membrane. The study aims to design a tympani thermometer. It compared the measurement results of the designed tool with ear thermometers that have been calibrated to get the error value. Based on the results, this prototype works well and has an error of 0.7°C in the left ear and an error of 0.24°C in the right ear.